There's Another Observation Unit?: A Case Series Survey of Second Level Observation Units. Issue 1 (March 2016) - Osborne, Anwar Dayan; Farrah, Hillary; Wheatley, Matthew; Baugh, Christopher
Abstract : Objectives: Observation units are dedicated areas in the hospital to deliver care to patients in observation status—those too risky to be immediately discharged following an emergency department evaluation but also clearly not in need of an inpatient admission. Observation units have been commonplace for several decades but in recent years some hospitals have begun to operate an additional observation unit with a distinct care delivery model and patient population. Methods: We conducted a survey between June 2014 and December 2014 to determine the prevalence and key operational characteristics of second level observation units in the US. We accessed the list serve of a large specialty organization to reach leaders likely to be directly operating or aware of the presence of a second level unit in their hospital. Results: We received 28 responses (response rate of approximately 10%). We found 8 second level OUs, with respondents able to provide detailed data for 6 of them. All were established within the past 5 years. Conclusions: Second level observation units are still relatively uncommon but are emerging as an extension of hospital-based observation services as an additional resource to cohort observation patients into a dedicated unit. These units share some similarities with traditional OUs, such as the nursing ratio of approximately 4:1 and the preponderance of chest pain pathways; however, they also differ in important ways around key metrics, such as length of stay, attending staffing coverage, and rate of subsequent inpatient admission. Additional study is needed both to fully characterize these units and their potential benefits.